2014
DOI: 10.1186/1756-6606-7-37
|View full text |Cite
|
Sign up to set email alerts
|

Vorinostat positively regulates synaptic plasticity genes expression and spine density in HIV infected neurons: role of nicotine in progression of HIV-associated neurocognitive disorder

Abstract: BackgroundHIV-associated neurocognitive disorder (HAND) is characterized by development of cognitive, behavioral and motor abnormalities, and occurs in approximately 50% of HIV infected individuals. In the United States, the prevalence of cigarette smoking ranges from 35-70% in HIV-infected individuals compared to 20% in general population. Cognitive impairment in heavy cigarette smokers has been well reported. However, the synergistic effects of nicotine and HIV infection and the underlying mechanisms in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 80 publications
2
36
1
Order By: Relevance
“…Synaptic plasticity is defined as a change in efficacy/strength of synapses (spine formation and maintenance of synaptic architecture) in response to the external stimuli. Neuronal plasticity dysregulation can be seen at the cellular level 4288 atluri et al by decreased spine density and synaptodendritic damage 6 and at the systemic levels with gray and white matter atrophy 7,8 in both cortical and subcortical regions. 9,10 Matrix metalloproteinases (MMPs) are a family of endopeptidases that play a major role in the degradation of most extracellular matrix proteins, wound healing, and tissue morphogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Synaptic plasticity is defined as a change in efficacy/strength of synapses (spine formation and maintenance of synaptic architecture) in response to the external stimuli. Neuronal plasticity dysregulation can be seen at the cellular level 4288 atluri et al by decreased spine density and synaptodendritic damage 6 and at the systemic levels with gray and white matter atrophy 7,8 in both cortical and subcortical regions. 9,10 Matrix metalloproteinases (MMPs) are a family of endopeptidases that play a major role in the degradation of most extracellular matrix proteins, wound healing, and tissue morphogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…An established laboratory protocol was used for infecting the SK-N-MC cells with HIV, 6 with slight modifications. Briefly, the SK-N-MC (1×10 5 cells) cells were grown overnight in six-well plates in the Dulbecco's Modified Eagle's Medium, and these cells were activated by treating with polybrene (10 µg/mL) for 6-7 hours before the infection.…”
Section: Hiv-1 Infection Of Human Sk-n-mc Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…19 Our group reports for the first time that vorinostat significantly activates latent HIV infection in the neuronal cells. 28 Different concentrations (0.5-5 µM) of vorinostat (solution phase) were tested for the latencybreaking ability; the results showed that a 1 µM concentration yields a significant difference in p24 value (data shown in Figure S5) and was used for the final formulation development. To confirm the efficacy of the nanoformulation after the magnetic-triggered release process after 24 hours, we conducted a p24 viral replication assay, the results of which showed ( Figure 9) that standard tenofovir (1 mg/mL solution), and MNPs-2BL nanoformulation showed equal p24 inhibition efficacy after the third day postinfection, thus suggesting that the integrity and efficacy of the drug are not lost after external magnetic application.…”
Section: Latency-breaking and In Vitro Antiviral Efficacy Of The Nanomentioning
confidence: 99%